Unleashing the furr-recovery method: Interacting with pets in teleworking replenishes the self’s regulatory resources: Evidence from a daily-diary study - Junça Silva, A. (International Journal of Environmental Research and Public Health, 2022)
This study is based on the conservation of resources theory and the recovery step model in order to further explore the furr-recovery method—a mechanism through which workers break their routine by taking micro-moments to interact with their “furry co-workers,” thus relieving their fatigue and tension or other negative affective states. Based on this, we argue that this method not only serves the purpose of restoring self-regulatory resources but also ameliorates mental health. Accordingly, this study aims to analyze how daily human–animal interactions during teleworking positively influence teleworkers’ mental health, via recovering their self-regulatory resources, at the within-person level. Full-time teleworkers completed multiple online surveys for 5 consecutive workdays (N = 211 × 5 = 1055 daily observations). Multilevel path analysis results showed that on days on which employees had more micro-moments to interact with their “furry co-workers” during the day, they experienced a higher self-regulatory capacity and felt better while working. In sum, the findings give support for the theoretical resource perspective of interacting with pets as an effective energy management strategy while at work. This research extends the theoretical understanding of regulatory resources as a cognitive mechanism that links HAIs to employee mental health. Moreover, the findings outlined here offer practical implications by highlighting the furr-recovery method, a method that teleworkers who own pets may use as a strategy during the working day to restore resources needed to be healthier.